Effects of environmental norfloxacin concentrations on the intestinal health and function of juvenile common carp and potential risk to humans - Zhao, Xue-Li; Li, Ping; Zhang, Si-Qi; He, Shu-Wen; Xing, Shao-Ying; Cao, Zhi-Han; Lu, Rong; Li, Zhi-Hua (Environmental pollution (1987), 2021)
Antibiotics are emerging pollutants in our environment. These treatments have been widely used for their low cost, convenient use, and prominent effects. However, the prolonged or excessive use of such drugs can cause toxicity in aquatic organisms. These effects include genotoxicity, metabolic alteration, delayed development and decreased immunity, which carry further risks for ecological systems. In the present study, juvenile common carp (Cyprinus carpio) were exposed to norfloxacin (NOR) for 42 days, with NOR concentrations ranging from 100 ng/L to 1 mg/L, to assess the effects of environmental concentrations of antibiotics, to investigate the effects of NOR on intestinal morphology, enzymatic activity, and transcriptomic levels of RNA in fish, as well as a risk assessment on human health was carried out. The results demonstrated that oxidative stress was induced, the barrier function of the intestine was damaged, and changes occurred in the expression of immune-related genes in fish chronically exposed to antibiotics. Moreover, NOR could affect the regulation of the NF-κB signaling pathway. Thus, environmental concentrations of antibiotics can influence the intestinal health of fish and potentially posing health risks to humans. Gene expression in intestine tissues of juvenile common carp after exposing to NOR for 42 days. [Display omitted] •Environmental levels of NOR could induced the oxidative stress in fish.•Environmental levels of NOR could damage the barrier function in fish.•Environmental levels of NOR could regulate the immune-related genes in fish.•Environmental levels of NOR has potentially posing health risks to humans.